Munhälsa hos patienter med cancerdiagnos: -en interventionsstudie av vårdpersonal och patienter Ett vårdutvecklingsprojekt hos Cancerfonden 2002-2004 - Paulsson, Gun (Socialmedicinsk tidskrift, 2007)
Patienter med cancerdiagnos är en speciell grupp där komplikationer, dels i samband med själva grundsjukdomen, dels i samband med de behandlingar patienten genomgår, påverkar munhälsan. Upprätthållandet av en god munhälsa är därför av största betydelse för både nutrition, tillfrisknande och välbefinnande. Munvård betraktas som en betydelsefull men eftersatt omvårdnadsåtgärd och överskuggas ofta av andra behov som upplevs som mer angelägna. Munhälsodokumentationen måste förbättras, men detta bör göras inom ramen för en generell förbättring av rutinerna runt omvårdnadsdokumentationen, vilken ofta uppvisar brister. Patients need to be asked questions by the health-care staff if oral problems are to be discovered in good time. In this project, the health-care staff assessed oral problems as being more serious than the patients did. We cannot expect patients, during the course of a serious illness, to take responsibility for their oral health. Routines therefore need to be created to ensure that oral problems are identified before they become so extensive that effective treatment is difficult to administer. This applies in particular to patients receiving chemotherapy and radiotherapy, as both the disease and the treatment lead to a gradual deterioration in the patient’s general condition. In this project, it was shown that the oral assessment instrument was practical for both nurses and auxiliary nurses. However, it probably needs to be linked to an oral health standard to provide the health-care staff with guidance on the oral health care measures that should be implemented for various oral problems. A standard of this kind was drawn up during the project, but its practicability still needs to be tested. Finally, the oral health documentation needs to be improved, but this should be done within the framework of a general improvement in the routines associated with health-care documentation, where shortcomings are frequently found. Keywords: cancer patients, nursing care, oral assessment guide, self assessed oral health